Translating Indigeneity at the University of Alberta - Malena, Anne; Tarif, Julie (TTR, 2018)
Over the last few years there has been an attempt to redress the asymmetrical relations between Canada’s First Nations, Métis, and Inuit people, and the non-Indigenous people in Canada. Post-secondary education plays a prominent role in this endeavour and many institutions across Canada are currently working on innovative ways to make their environment more inclusive, or what is called “Indigenizing” the academy. This study focuses on how the University of Alberta (Edmonton) is meeting this challenge and argues that a form of activist translation needs to be an important part of this endeavour in order to redress damages caused by colonialism.